Generation of tandem direct duplications by reversed-ends transposition of maize ac elements. - Jianbo Zhang; Tao Zuo; Thomas Peterson (PLoS Genetics, 2013)
Tandem direct duplications are a common feature of the genomes of eukaryotes ranging from yeast to human, where they comprise a significant fraction of copy number variations. The prevailing model for the formation of tandem direct duplications is non-allelic homologous recombination (NAHR). Here we report the isolation of a series of duplications and reciprocal deletions isolated de novo from a maize allele containing two Class II Ac/Ds transposons. The duplication/deletion structures suggest that they were generated by alternative transposition reactions involving the termini of two nearby transposable elements. The deletion/duplication breakpoint junctions contain 8 bp target site duplications characteristic of Ac/Ds transposition events, confirming their formation directly by an alternative transposition mechanism. Tandem direct duplications and reciprocal deletions were generated at a relatively high frequency (~0.5 to 1%) in the materials examined here in which transposons are positioned nearby each other in appropriate orientation; frequencies would likely be much lower in other genotypes. To test whether this mechanism may have contributed to maize genome evolution, we analyzed sequences flanking Ac/Ds and other hAT family transposons and identified three small tandem direct duplications with the structural features predicted by the alternative transposition mechanism. Together these results show that some class II transposons are capable of directly inducing tandem sequence duplications, and that this activity has contributed to the evolution of the maize genome.